Health Benefits of the Mediterranean Diet: Metabolic and Molecular Mechanisms. (13th December 2017) - Tosti, Valeria; Bertozzi, Beatrice; Fontana, Luigi
Abstract: Consuming a Mediterranean diet rich in minimally processed plant foods has been associated with a reduced risk of developing multiple chronic diseases and increased life expectancy. Data from several randomized clinic trials have demonstrated a beneficial effect in the primary and secondary prevention of cardiovascular disease, type 2 diabetes, atrial fibrillation, and breast cancer. The exact mechanism by which an increased adherence to the traditional Mediterranean diet exerts its favorable effects is not known. However, accumulating evidence indicates that the five most important adaptations induced by the Mediterranean dietary pattern are: (a) lipid-lowering effect, (b) protection against oxidative stress, inflammation and platelet aggregation, (c) modification of hormones and growth factors involved in the pathogenesis of cancer, (d) inhibition of nutrient sensing pathways by specific amino acid restriction, and (e) gut microbiota-mediated production of metabolites influencing metabolic health. More studies are needed to understand how single modifications of nutrients typical of the Mediterranean diet interact with energy intake, energy expenditure, and the microbiome in modulating the key mechanisms that promote cellular, tissue, and organ health during aging.